Harmonisasi Prinsip Hukum Tanggung Jawab Sosial-Lingkungan Perusahaan Pertambangan Mineral dan Batubara Dalam Peraturan Perundang-Undangan Di Indonesia - Rifda Afifah; Sodikin Sodikin (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThe research was conducted in an effort to find concretisation of the legal principles that apply to the provisions concerning social and environmental responsibility of mineral and coal mining companies in Indonesian laws and regulations. In addition to examining the legal consequences for any corporation that does not carry out these provisions. Specifically, this research seeks to discuss the content of rules and harmonization of regulations governing social and environmental responsibility of mineral and coal mining companies. Because in practice the exploration has a very significant impact on the environmental and social conditions around the company. This research is a normative qualitative research (normative Legal Research) which is carried out by reviewing the prevailing statutory system (statue aproach). The results showed that the harmonization of laws and regulations was found to have the principle of social responsibility that is mandatory. However, for any corporation that does not carry out its obligations is still only subject to administrative sanctions and is not equipped with other law enforcement instruments, both criminal and civil.Keywords: Environmental Social Responsibility, Harmonization, Legal Certainty